2007
DOI: 10.1080/15368370601185888
|View full text |Cite
|
Sign up to set email alerts
|

Light and Electron Microscope Studies of Effects of 50 Hz Electromagnetic Fields on Preincubated Chick Embryo

Abstract: We investigated the effects of an electromagnetic field (EMF) of 50 Hz, 1.33-7.32 mT on sections of preincubated white leghorn chicken embryos using light, SEM and TEM microscopes. Five hundred healthy, fresh, and fertilized eggs (55-65 g) were divided into three groups of experimental (n = 18-20), control (n = 60), and sham (n = 50). Experimental eggs (inside the coil) were exposed to 15 different intensities (1.33-7.32 mT) for morphological surveys and to the known most effective intensities for light, scann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Coil was located in an east -west direction, magnetic flow was parallel to long axis of embryo's body (longitude 351400 and latitude 511250) and perpendicular to long axis of the eggs (DiCarlo et al, 2000;Shams Lahijani et al, 2007, 2009Ubeda et al, 1994). A system of air condition (one, 5 cm from the entrance of coil and others beneath the coil) ventilated the coil chamber.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Coil was located in an east -west direction, magnetic flow was parallel to long axis of embryo's body (longitude 351400 and latitude 511250) and perpendicular to long axis of the eggs (DiCarlo et al, 2000;Shams Lahijani et al, 2007, 2009Ubeda et al, 1994). A system of air condition (one, 5 cm from the entrance of coil and others beneath the coil) ventilated the coil chamber.…”
Section: Methodsmentioning
confidence: 99%
“…A system of air condition (one, 5 cm from the entrance of coil and others beneath the coil) ventilated the coil chamber. Frequency was always 50 Hz, with 3 most effective flux intensities of 1.33, 2.66, and 7.32 mT (Shams Lahijani et al, 2007, 2009.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are numerous studies showing that EMF exposure of male rat/mice affects testicular architecture , spermatogenesis, sperm motility, leydig cell reduction, increased apoptosis of germ cells and in general subfertility and or infertility ( Khaki et al 2006;Lee et al 2004;Soleimani Rad and Katebi 1997;Devita et al 1995;Lokmatova 1993). In human and animal studies, it has been reported that female exposure to EMF cause some adverse effects and reviewed the potential effect of EMFs on infertility, implantation rate, number of living fetuses, sex ratio, miscarriages, premature births, growth retardation, low birth weight, congenital malformations and prenatal deaths (Roshangar and Soleimani Rad 2007;Lahijani et al 2007;Feychting et al 2005;Chiang et al 1995;Huuskonen et al 1993;Juutilainen et al 1993;Mc Govern et al 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Based on our previous published reports, studying the effects of EMFs' on preincubated chick embryos as a whole and at specific levels (Shams Lahijani et al, 2007, 2009Shams Lahijani and Ghafoori, 2000;Shams Lahijani and Rajabi Moham, 2000;Shams Lahijani and Sajadi, 2004;Shams Lahijani and Sharifnia, 1999), the aim of this study was to investigate the effects of the most effective intensity of 50 Hz EMF (7.32 mT) (Shams Lahijani et al, 2009) on the process of apoptosis, and its genetical and molecular effects on the livers of preincubated chicken embryos.…”
Section: Introductionmentioning
confidence: 99%